2009
DOI: 10.1177/097226290901300404
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Consumer Sales Promotions on Brand Loyal and Brand Switching Segments

Abstract: Sales promotions are generally looked at as tools that undermines the brand; yet a tool that is necessarily meant to speed up sales. Consumer sales promotion take up a large share of the total marketing expenditure despite which it remains an area that still attracts attention as an essential component of the promotion mix meant to increase short term sales. It is therefore not surprising that most of the marketers resort to sales promotions to attract the competitor's market share. The present paper reports t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 36 publications
2
22
0
3
Order By: Relevance
“…Prior studies have reported the important role played by promotion in influencing consumer behavior (Sood and Kathuria, 2005). Even though generally, the sales promotion is viewed as a destructive tool in promoting certain brands (Nagar, 2009), companies believe that it must be done and is intended to accelerate sales. In many cases, sales promotion takes a big part of total marketing expenditure, and it remains as an area that still attracts attention and plays an important component of the promotion mix that is intended to increase short-term sales.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have reported the important role played by promotion in influencing consumer behavior (Sood and Kathuria, 2005). Even though generally, the sales promotion is viewed as a destructive tool in promoting certain brands (Nagar, 2009), companies believe that it must be done and is intended to accelerate sales. In many cases, sales promotion takes a big part of total marketing expenditure, and it remains as an area that still attracts attention and plays an important component of the promotion mix that is intended to increase short-term sales.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In many cases, sales promotion takes a big part of total marketing expenditure, and it remains as an area that still attracts attention and plays an important component of the promotion mix that is intended to increase short-term sales. Therefore, it is not surprising that most marketers use sales promotions to attract market share of competitors (Nagar, 2009). The study of Kahn and Louie (1990) reports that the effect of sales promotion on consumers who frequently make the brandswitching decisions has encouraged consumers to be attracted to the product of a certain brand, which is in a sales promotion program.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, retailers are trying harder to cope with the changing competitive environment by using different promotional tools and understanding the preferences of customers. Customers' preferences and commitment for a brand or a product play a vital role in building customer loyalty as it has been proved earlier by Nagar (2009), that only repeat purchasers are profitable. Customer's commitment adds to the profitability of the businesses but it is not every purchase that leads towards customer loyalty and profitability.…”
Section: Customer Loyaltymentioning
confidence: 99%
“…According to (Nagar, 2009) it has been recognized in literature that only customers with repeat purchases are profitable. Is not this all repeat purchase online to engage consumers with the brand?…”
Section: Sales Promotionsmentioning
confidence: 99%